2014
DOI: 10.1039/c4cy00504j
|View full text |Cite
|
Sign up to set email alerts
|

Selective hydrogenation of levulinic acid to valeric acid and valeric biofuels by a Pt/HMFI catalyst

Abstract: Valeric acid and valeric biofuels are obtained in high yield by direct hydrogenation of levulinic acid catalyzed by Pt/HMFI under relatively mild conditions (2 or 8 bar H2, 200 °C), driven by cooperation of the metal and support Brønsted acid sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 32 publications
4
84
0
Order By: Relevance
“…The product distributions obtained using these catalysts showed the formation of ring opened compounds over 5wt.%Ni/TiO 2 catalyst, whilst no ring opening products are observed for 20wt.%Ni/TiO 2 catalyst. These results are in good correlation with results by Kenichi and co-workers [31], who reported that ring opening of GVL occurs on Brønsted acid sites. It is unlikely that the hydroxyl groups on bare TiO 2 surface are active, as a test experiment on the activity of pure TiO 2 showed nil conversion of GVL to ring opened compounds.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The product distributions obtained using these catalysts showed the formation of ring opened compounds over 5wt.%Ni/TiO 2 catalyst, whilst no ring opening products are observed for 20wt.%Ni/TiO 2 catalyst. These results are in good correlation with results by Kenichi and co-workers [31], who reported that ring opening of GVL occurs on Brønsted acid sites. It is unlikely that the hydroxyl groups on bare TiO 2 surface are active, as a test experiment on the activity of pure TiO 2 showed nil conversion of GVL to ring opened compounds.…”
Section: Discussionsupporting
confidence: 93%
“…the acidity and hydrogenation character of the metal and the support material that possess stronger Brønsted acid sites (BAS) is not suitable for metal in the hydrogenation of LA to GVL. Hence, choice of the support is crucial as it plays an important role in deciding the required metal/acidic sites for reaction [31,32]. Mechanisms proposed earlier were in two routes based on the reaction temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Note, that the levulinic acid ester formation decreases the GVL yields much more if Ni catalysts are used because noble metal based catalysts also catalyze the GVL formation starting from levulinic acid esters and therefore in those cases often alcohols as solvents are used. [17,44] A longer reaction time for the hydrogenation of LA to GVL in presence of an alcohol did not increase the GVL yield, also not once 100 % LA is converted. Note that no 4-hydroxypentanoic acid was found, also not by NMR (not shown).…”
Section: Conversion Of La To Gvl In Different Solventsmentioning
confidence: 92%
“…These initial results are highly promising since significantly more harsh reaction conditions (200°C, 30-40 bar H 2 ) are generally reported in the literature for these reactions to achieve similar yields of γ-valerolactone with catalysts containing transition metals like Pt, Ru and Rh. 29,30,35,36 More detailed exploration of the γ-valerolactone formation from methyl levulinate and derivatives will be the subject of future work.…”
Section: Selective Hydrogenation Of Arenes With Rhnps/pvpmentioning
confidence: 99%